Peran Orang Tua dalam Mewujudkan Generasi Unggul di Era Digital - Lestari, Endang; Arifin, Muh. Zainul (STKIP PGRI Ponorogo Press, 2024)
Parents are the main actors in the success of children’s education. Especially in the digital era, parents have to be one step ahead of their children. The aim of this research is to examine the role of parents in producing superior early childhood children in the digital era. The method in this research is qualitative with a library research design. Data are collected by reviewing literature and references and then connected to research goals. Research results regarding the importance of synergy between educators and parents to produce excellent children in the digital era are urgently needed. The steps that teachers and parents need to take in producing a excellent generation in the digital era are by providing a sense of security, self-confidence, encouragement and praise, respecting the process and not demanding only the results, not forcing children to do activities beyond their abilities, respecting achievements, don’t emphasize children’s mistakes, giving children the opportunity to solve their own problems, and the importance of training children’s independence.